Kajian Semiotika Pada Desain Kartu Pos Got?chi Forumuk?do Prefektur Toyama - Theresia, Martha; Rauh Artana, I Nyoman; Wiriani, Ni Made (Humanis; Vol 23 No 2 (2019), 2019)
The tittle of this thesis is “Study of Semiotics On Got?chi Forumuk?do Postcard Design in Toyama Prefecture”. The purpose of this research is to reveal signifier and signified on Got?chi Forumuk?do postcard design in Toyama Prefecture from verbal and visual structure signs. The analysis of this research uses Semiotics Theory according to Sudjiman and Zoest (1996) used for reveal signifier and signified and verbal and visual structure. The data source using 9 (nine) Got?chi Forumuk?do postcards in Toyama Prefecture released from 2009 to 2017/2018. Data collection uses library study method and then observation and note taking technique. The analysis uses descriptive analytic method and informal method according to (Sudaryanto 1993:135) . The result shows that the interaction of verbal and visual signs creates verbal and visual messages that are interrelated. Through on the signs of verbal and visual is able to visualized signifier and signified from each postcard designs so that the messages can be well conveyed.